Mechanism Of Alpha Mangosteen As An Inhibitor Of Matrixmetalloproteinase-1 In Skin Cancer By In-Silico Study - Fristiohady, Adryan; Arfan, Arfan; Asasutjarit, Rathapon; Haruna, Lidya Agriningsih; Purnama, La Ode Muhammad Julian; Sahidin, Idin; Malik, Fadhliyah; Kirana, Rezky Marwah; Kardin, Laode; Idrus, Loly Subhiaty; Malaka, Muhammad Hajrul (Jurnal Mandala Pharmacon Indonesia, 2024)
?-mangostin (?-MG) is a metabolite of xanthones isolated from fruit of Garcinia mangostana Linn pericarps. Skin cancer is one of the most common malignancies affecting many people. The development of skin cancer is mainly due to intermittent or long-term exposure to ultraviolet (UV) radiation resulting in reduced cell-mediated immune response, production of reactive oxygen species (ROS), and DNA changes. Increased levels of ROS can induce the production of matrix metalloproteinases (MMPs). ?-MG showing potential as an anti-metastatic agent with reduced the expression of MMP-1. This study aims to determine the affinity and stability profiles of ?-MG as anti-skin cancer by applying the In-Silico method. Molecular simulation of ?-MG was successfully docked to the MMP-1. ?-MG showed stable results after 100 ns molecular dynamics simulation based on the root mean square deviation (RMSD) and the root mean squared fluctuation (RMSF). The binding energies of the xanthone derivatives were calculated using the MM/PBSA method.